Copahue geothermal system: a volcanic environment with rich extreme Prokaryotic biodiversity - Urbieta, María Sofía (2015)
The Copahue geothermal system is a natural extreme environment located at the northern end of the Cordillera de los Andes in Neuquén province in Argentina. The geochemistry and consequently the biodiversity of the area are dominated by the activity of the Copahue volcano. The main characteristic of Copahue is the extreme acidity of its aquatic environments; ponds and hot springs of moderate and high temperature as well as Río Agrio. In spite of being an apparently hostile location, the prokaryotic biodiversity detected by molecular ecology techniques as well as cultivation shows a rich and diverse environment dominated by acidophilic, sulphur oxidising bacteria or archaea, depending on the conditions of the particular niche studied. In microbial biofilms, found in the borders of the ponds where thermal activity is less intense, the species found are completely different, with a high presence of cyanobacteria and other photosynthetic species. Our results, collected during more than 10 years of work in Copahue, have enabled us to outline geomicrobiological models for the different environments found in the ponds and Río Agrio. Besides, Copahue seems to be the habitat of novel, not yet characterised autochthonous species, especially in the domain Archaea.